Recent Developments in Mesoporous Silica Nanoparticles for Tumor Theranostic Applications - Wang, Xuerui; Zheng, Mengyuan; Raza, Faisal; Liu, Yuhao; Wei, Yiqi; Qiu, Mingfeng; Su, Jing (Current Pharmaceutical Design, 2022)
Due to the advantages of adjustable pore size, easy surface modification, high biocompatibility, and so on, mesoporous silica nanoparticles (MSNs) have attracted significant attention. Moreover, they are widely used in the fields of biology and medical research, mostly focusing on drug and gene delivery and bioimaging. This review introduces several commonly used synthetic methods of MSNs and the latest progress of MSNs in tumor therapy and diagnosis, mainly including the study about modified MSNs as drug carriers and the application of MSNs in bioimaging. The deficiencies of MSNs’ application and prospects for its future clinical transformation are also discussed.
Keywords: gene delivery